Stratégies de publication scientifique - Volland-Nail, Patricia (éditions Quae, 2013)
Publish or perish! Researchers are very familiar with this injunction. But what should be published, where, when, how and with whom? Some questions to which this book attempts to find answers. Filled with numerous links and videos, this electronic book will help the researcher to navigate through the complex, moving world of scientific publication.